Galectin-1 prevents pathological vascular remodeling in atherosclerosis and abdominal aortic aneurysm - Roldán Montero, Raquel (2022)
Pathological vascular remodeling is the underlying cause of atherosclerosis and abdominal aortic aneurysm (AAA). Here, we analyzed the role of galectin-1 (Gal-1), a β-galactoside-binding protein, as a therapeutic target for atherosclerosis and AAA. Mice lacking Gal-1 (Lgals1-/-) developed severe atherosclerosis induced by pAAV/D377Y-mPCSK9 adenovirus and displayed higher lipid levels and lower expression of contractile markers of vascular smooth muscle cells (VSMCs) in plaques than wild-type mice. Proteomic analysis of Lgals1-/- aortas showed changes in markers of VSMC phenotypic switch and altered composition of mitochondrial proteins. Mechanistically, Gal-1 silencing resulted in increased foam cell formation and mitochondrial dysfunction in VSMCs, while treatment with recombinant Gal-1 (rGal-1) prevented these effects. Furthermore, rGal-1 treatment attenuated atherosclerosis and elastase-induced AAA, leading to higher contractile VSMCs in aortic tissues. Gal-1 expression decreased in human atheroma and AAA compared to control tissue. Thus, Gal-1-driven circuits emerge as potential therapeutic strategies in atherosclerosis and AAA.